Market Abuse Directive and Insider Trading: Evidence from Italian Tender Offers - Riccardo Ferretti; Pierpaolo Pattitoni; Roberto Patuelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
This study analyzes the effectiveness of the Market Abuse Directive (MAD) in reducing possible profits from insider trading during voluntary tender offers with the purpose of delisting initiated by controlling shareholders. Exploiting the quasi-experimental setting provided by the introduction of the MAD, our event-study analysis on the Italian market suggests that the new regulation did not produce appreciable effects on the magnitude of abnormal returns and volumes noted before the announcement of a tender offer. Multivariate econometric analyses based on regression and matching methods confirm this result. However, poolability tests reveal that the MAD has changed the manner in which corporate characteristics influence the capacity of insiders to make profit. We interpret our results considering the choice problem of the optimal amount of insider trading, when comparing the marginal costs and benefits of the illegal activity.
Keywords: K2; K4; G34; G14; 330